2019
DOI: 10.1007/s10803-019-04122-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Intellectual and Memory Abilities of Older Autistic Adults with Typically Developing Older Adults Using WAIS-IV and WMS-IV

Abstract: This study aimed to compare cognitive and memory abilities between older adults with and without autism over the age of 50. Twenty-eight individuals with autism and 29 typically developing (TD) older adults took part in the current study. Participants’ cognitive and memory abilities were assessed by WAIS-IV and WMS-IV. Older autistic adults were found to have poorer performance in processing speed and visual working memory, but they performed at a similar level as TD controls in all other domains. Poorer proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 60 publications
6
41
1
1
Order By: Relevance
“…Thus, in older autistic men with a late adulthood ASC diagnosis and (above) average IQ, EF problems in daily life are clearly reported on, while this is not reflected in their cognitive test performance and is not differentially impacted by their age. The consistency of findings across the current study and the Davids et al (2016) study, is in sharp contrast with the lack of consistency across the broader range of studies including older autistic adults (Braden et al 2017;Geurts and Vissers 2012;Lever and Geurts 2016a, b;Powell et al 2017;Tse et al 2019;Walsh et al 2019). This inconsistency in findings could be due to differences in sample characteristics (age, sex, IQ level), type of cognitive tasks included, chosen statistical analyses, and how intelligence levels were accounted for.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…Thus, in older autistic men with a late adulthood ASC diagnosis and (above) average IQ, EF problems in daily life are clearly reported on, while this is not reflected in their cognitive test performance and is not differentially impacted by their age. The consistency of findings across the current study and the Davids et al (2016) study, is in sharp contrast with the lack of consistency across the broader range of studies including older autistic adults (Braden et al 2017;Geurts and Vissers 2012;Lever and Geurts 2016a, b;Powell et al 2017;Tse et al 2019;Walsh et al 2019). This inconsistency in findings could be due to differences in sample characteristics (age, sex, IQ level), type of cognitive tasks included, chosen statistical analyses, and how intelligence levels were accounted for.…”
Section: Discussioncontrasting
confidence: 65%
“…Moreover, their proxies also observed that the autistic adults experienced daily life EF problems. In yet another recent and similar study (Tse et al 2019; N ASC = 28, N non-ASC = 27, age 50-72 years) the ASC group was generally slower and performed less well on visual WM as compared to the non-ASC group. Unfortunately, in these studies age-related differences were not explored.…”
mentioning
confidence: 71%
See 3 more Smart Citations